Eksplorasi Dinamika Sosial Melalui Analisis Sentimen Tagar #KaburAjaDulu di Media Sosial Tiktok - Meylia Arifah Salsa; Irhamna Irhamna; Dhabita Azka Lubis; Fajar Wira Aqmalsah; Tiara Putri Sayani; Farhan Ihromi Lubis; Ibnu Mazlan (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
This study explores the social and psychological dynamics of the collective expression of the Indonesian youth through the hashtag #KaburAjaDulu on TikTok social media, which reflects their concerns about inequality in access to work and lack of opportunities for self-development. This study uses qualitative methodology and a virtual ethnography approach to analyze data, covering social interactions and meaning construction in virtual communities. Primary data sources involve real-time monitoring using tools such as Brand24, which captures the frequency and sentiment of posts. Secondary data sources are obtained from literature related to labor migration, digital expression, and network society theory. Data collection techniques combine passive online observation and thematic classification, while data analysis is carried out through content analysis to identify dominant discourse patterns and sentiments. Data validity is tested using source triangulation, comparing netnography findings with scientific references and policy documentation. The results show that the hashtag #KaburAjaDulu is not just an expression of jokes, but a symbol of structural alienation and the aspirations of the young generation to seek better life opportunities abroad. The discussion highlights the implications of this social critique for migration policies and the protection of migrant workers. The conclusion emphasizes the importance of adaptive government responses and more inclusive policies to address the aspirations of the younger generation.